Perlindungan Hukum Bagi Penerima Waralaba Dalam Pemutusan Perjanjian Secara Sepihak - Rappe, Arifin; Kuahaty, Sarah Selfina; Pesulima, Theresia Louize (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: A franchise agreement is a special agreement or also called an anonymous agreement, because it is not found in the Civil Code.Purposes of the Research: This writing aims to examine and discuss legal protection for franchisees related to unilateral termination of agreements made by the franchisor. Methods of the Research: The method used is a normative juridical research method using a statutory approach and a conceptual approach.Results of the Research: The results obtained from the research, the impact of unilateral termination of the agreement causes franchisees to sue and resolve disputes by way of deliberation by giving a warning or subpoena and also through out-of-court channels in accordance with Law Number 30 of 1999 paragraph (1) concerning Arbitration and alternative dispute resolution. This is also inseparable from the franchisor's responsibility for unilaterally terminating the agreement to the franchisee and the franchisee has the right to claim losses in accordance with Article 1243-1252 of the Civil Code.